Enhancement of Phosphorus Sorption onto Peanut shell by Means of Aluminum and Iron Oxide Coatings - Ali, Hazhar Jalal; Rasheed, Muhammed Saeed; Hawramy, Omran A; Saeed, Aya Muhammed (Kurdistan Journal of Applied Research, 2024)
Phosphorus serves as a crucial nutrient for the organisms. Still, the discharge of high levels of phosphate concentrations into limited aquatic environments leads to the phenomenon known as eutrophication, which subsequently leads to the degradation of the overall water quality. In this study the capacity of the peanut shell, Al-coated and Fe-coated is determined in relating by adding 10, 20, and 30, 40 mg P L-1 as (KH2PO4) to 1.0 g of each sample and shaking for 2, 6, 12, and 24 h and at pH ranged between 4.6, 5.2, 6.3 and 7.8. At the end of each period, the suspension was filtered and analyzed which presents the concentration of equilibrium P. The maximum P adsorption of 28.9±0.07 and 50.6±0.49% was recorded for 24 h of incubation and at pH (4.6) with an Al-coated peanut shell respectively. The findings of this study demonstrated that the adsorption of phosphorus (P) increased as the duration of incubation increased. At the same time, it decreased with a decrease in the pH of the solution. Furthermore, the outcomes indicated that the Freundlich model provided the best fit for the data, based on higher R2 values ranging from 0.9867 to 0.9938, in comparison to the range of 0.9659 to 0.9904 observed for the Longmuir model. These results suggested that peanut shells coated with Al can be used to remove high amounts of P in the solution. Also, the removal resulted from the physical adsorption of P rather than a chemical reaction.